A technique to remove a stable all-polyethylene cemented acetabular liner in revision hip arthroplasty: A case report - Judas, F (2015)
INTRODUCTION: The removal of a well-fixed acetabular component in a total hip arthroplasty can cause bone fractures, excessive bleeding, as well as extended bone loss. The reimplantation of a new acetabular component may be compromised. PRESENTATION OF CASE:We report a technique using 2 cork-screws for removal a stable cemented acetabular component for the treatment of a recurrent dislocation of a cemented total hip arthroplasty, due to acetabular malposition. DISCUSSION: A diversity of approaches and tools has been used for extraction ofthe acetabular prosthesis. Using 2 cork-screws it is possible to create fissures and fractures into the cement mantle, and greater manual control is obtained facilitating the manipulation of the acetabular component in different directions. The cup-cemented bond can be disrupted, the host bone is preserved and the risks of complications are minimized. CONCLUSION: This technique is simple, available in any environment, reproducible, non-costly, nontiming consuming and safe.